Corporate carbon emission statements - Stefan Reichelstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Current corporate disclosures regarding carbon emissions lack commonly accepted accounting rules. The accrual accounting system for carbon emissions described here is grounded in the rules of historical cost accounting for operating assets, enabling the preparation of balance sheets and flow statements. The asset side of the balance sheet reports the carbon emissions embodied in operating assets. The liability side conveys the firm's cumulative direct emissions into the atmosphere as well as the cumulative emissions embodied in goods acquired from suppliers less those sold to customers. Flow statements report the cradle-to-gate carbon footprint of goods sold during the current period. Taken together, balance sheets and flow statements generate multiple indicators of a company's past, current and future performance with regard to carbon emissions.
Keywords: M41; M48; Q53; Q54; 330; Treibhausgas-Emissionen; Umweltbericht; Umweltmanagement; Betriebswirtschaftliches Ziel; Deutschland